2021
DOI: 10.1371/journal.pone.0257203
|View full text |Cite
|
Sign up to set email alerts
|

Response of maize and common bean to spatial and temporal differentiation in maize-common bean intercropping

Abstract: An experiment on maize (Zea mays)-common bean (Phaseolus vulgaris L.) intercropping was conducted for two years (2014 and 2016) at two locations in North western Ethiopia with the objective of determining the spatial arrangement and planting date of common bean. Common bean intercropped with maize at three planting dates (simultaneously with maize, at emergence and knee height of maize) in two spatial arrangements (alternate and paired arrangements).The experimental design was factotrial randomized complete bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…This system is profitable and therefore recommended for a resource-poor producer who wishes to increased income with reduced N fertilize cost. Similarly, Bitew et al (2021) found that reduce competition between intercrops components by changes planting date had significant economic benefit expressed with higher MAI. The high economic advantage (IAI and MAI) for common beans/maize relay intercropping might be better utilization of growth resources between maize and common beans combinations (Alemayehu et al, 2017(Alemayehu et al, , 2018Bitew et al, 2021;Suárez et al, 2022).…”
Section: Economic Evaluationmentioning
confidence: 90%
See 2 more Smart Citations
“…This system is profitable and therefore recommended for a resource-poor producer who wishes to increased income with reduced N fertilize cost. Similarly, Bitew et al (2021) found that reduce competition between intercrops components by changes planting date had significant economic benefit expressed with higher MAI. The high economic advantage (IAI and MAI) for common beans/maize relay intercropping might be better utilization of growth resources between maize and common beans combinations (Alemayehu et al, 2017(Alemayehu et al, , 2018Bitew et al, 2021;Suárez et al, 2022).…”
Section: Economic Evaluationmentioning
confidence: 90%
“…Intercropping increase maize yield by more than 12.5% (Latati et al, 2016). Optimized planting time of common beans reduce the yield difference between intercropped and sole maize by enhancing maize resilience toward asymmetric competition (Bitew et al, 2021).…”
Section: Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of 50% inorganic fertilizer and 50% liquid organic fertilizer showed the optimum bulb weight of 54.33 g (Table 2). This is because the combination of organic and inorganic fertilizers can reduce the decline in soil health and increase and maintain agricultural productivity [16].…”
Section: Shallot Yieldmentioning
confidence: 99%
“…Maize-bean intercrop has been found to consistently increase land productivity by 20-150% compared to sole cropping (Alemayehu et al, 2017;Bitew et al, 2021;Kutu and Asiwe, 2010;Morgado and Willey, 2003;Ndungu-Magiroi et al, 2017). Based on land equivalent ratios (LERs), farmers practicing intercrop utilise less land to produce the same amount of crop as is produced under sole cropping on a relatively larger land.…”
Section: Introductionmentioning
confidence: 99%